1996
DOI: 10.1093/ije/25.6.1262
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Anaemia in Children with a High Prevalence of Haemoglobinopathies: Implications for Screening

Abstract: For populations such as ours most anaemia is not due to iron deficiency and a single Hb determination is therefore not acceptable for a presumptive diagnosis of IDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…8 In Thailand, iron deficiency anemia was prevalent only among the preschool-aged children (19%), while there was no evidence of anemia related to iron deficiency in the school-aged children. 2 The Côte d'Ivoire analyses found an association with cellular iron deficiency and anemia in schoolaged children at baseline, 6 and a negative association with Hb concentration in the prospective study. 29 Importantly, the iron parameters (ferritin and soluble transferrin receptor) were associated with inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…8 In Thailand, iron deficiency anemia was prevalent only among the preschool-aged children (19%), while there was no evidence of anemia related to iron deficiency in the school-aged children. 2 The Côte d'Ivoire analyses found an association with cellular iron deficiency and anemia in schoolaged children at baseline, 6 and a negative association with Hb concentration in the prospective study. 29 Importantly, the iron parameters (ferritin and soluble transferrin receptor) were associated with inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 87%
“…Comparable rates have been found by various studies in low-income populations, but with relatively less evidence for this age group compared with other vulnerable groups. [2][3][4][5][6] It is widely recognized that there are multiple causes of anemia, although the proportional representation of these various risk factors is less well characterized. 7 Differences across populations are further complicated by environmental and demographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The results from other researches in developing countries showed that the prevalence of anemia in African and Southeast Asian countries and India is higher than in Saudi Arabia [22,23] . In addition, the prevalence of anemia (Hb < 11 g/dl) in urban slum areas of India was 76% [24] , and it is reported to be 27% in children between the ages of 6 months and 13 years in northern Thailand [25] . Also, the prevalence of anemia in South Cameroon in children younger than 3 years was reported to be 42% and in children between 3-5 years old, it was reported to be 21% [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of other nutrients such as vitamins A, C, B 2 , B 12 and folic acid may also cause anemia (Fishman et al 2000). Other identified non-nutritional causes of anemia include malaria (Stoltzfus et al 1996, Dreyfuss et al 2000, hookworm infestation (Stoltzfus et al 1996), chronic infection and inflammation (Jansson et al 1986), and hemoglobinopathies such as thalassemia (Linpinsarn et al 1996).…”
Section: Introductionmentioning
confidence: 99%